93Nb NMR investigation and computer simulation of the Mg Ion localization in LiNbO3 - Yevdokimov, S. V.; Yatsenko, A. V.; Sugak, D. Yu.; Solskii, I. M. (Видавництво Львівської політехніки, 2012)
The angular dependences of the linewidth of the 93Nb NMR spectrum central transition is experimentally investigated for the LiNbO3 crystal with congruent composition and for the samples with two various Mg concentrations. Due to the computer simulation of the NMR spectra according some scenario of Mg incorporation in the LNbO3 structure, it has been concluded that the defect complexes ( Li 2 MgL+i + V ) with the Li vacancies are realized when the Mg concentration is less then threshold.
Keywords: LiNbO3:Mg; NMR; defect structure